2020
DOI: 10.1007/s00423-020-01998-6
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with the Kono-S anastomosis in Crohn’s disease of the terminal ileum—a cohort study

Abstract: Purpose The most frequent long-term complication after ileocecal resection in Crohn’s disease is anastomotic recurrence and subsequent stenosis. Recurrence typically begins at the site of the anastomosis, raising the question of whether the surgical technique of the anastomosis could affect recurrence rates. Kono-S anastomosis is a hand-sewn antimesenteric functional end-to-end anastomosis that offers a wide lumen that is well accessible for endoscopic dilatation. The purpose of our study is to review the rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Based on the results, our analysis supports the further evaluation of the Kono-S anastomosis technique following ICR in patients with Crohn’s disease in clinical routine in non-selective patient cohorts. In line with previous small studies focusing mainly on the perioperative morbidity of the Kono-S anastomosis [ 19 , 20 , 21 ], the rates of complications in our cohort were comparable between both groups, including the operating time and length of hospital stay ( Table 2 ). Furthermore, while our data demonstrated a clear trend towards decreased rates of disease recurrence, a multicenter study even demonstrated a five-year surgical recurrence-free survival rate of 98.6% in Japan [ 22 ].…”
Section: Discussionsupporting
confidence: 89%
“…Based on the results, our analysis supports the further evaluation of the Kono-S anastomosis technique following ICR in patients with Crohn’s disease in clinical routine in non-selective patient cohorts. In line with previous small studies focusing mainly on the perioperative morbidity of the Kono-S anastomosis [ 19 , 20 , 21 ], the rates of complications in our cohort were comparable between both groups, including the operating time and length of hospital stay ( Table 2 ). Furthermore, while our data demonstrated a clear trend towards decreased rates of disease recurrence, a multicenter study even demonstrated a five-year surgical recurrence-free survival rate of 98.6% in Japan [ 22 ].…”
Section: Discussionsupporting
confidence: 89%
“…The 5 and 10-year cumulative surgical recurrence rate were both 1.7%, with surgical recurrence occurring in only two Japanese patients. Since then a number of case reports, case series and retrospective studies with comparison to historical patients undergoing traditional anastomotic techniques have been published and demonstrated encouraging results (78)(79)(80)(81)(82). A retrospective study by Shimada et al published in 2019 compared 117 patients who underwent Kono-S anastomosis to 98 patients who underwent HEEA (83).…”
Section: Kono-s Anastomosismentioning
confidence: 99%
“…Then, 7‐cm long longitudinal enterotomies are created at the antimesenteric aspect, beginning 1 cm from the supporting column; the anastomoses of the bowels are then constructed transversely in a hand‐sewn fashion 111 . Several cohort studies and one randomized controlled trial have supported the use of this technique for reducing the postoperative recurrence rate 112–114 …”
Section: Advances In Operative Proceduresmentioning
confidence: 99%
“… 111 Several cohort studies and one randomized controlled trial have supported the use of this technique for reducing the postoperative recurrence rate. 112 , 113 , 114 …”
Section: Advances In Operative Proceduresmentioning
confidence: 99%